Effects of laser pulse duration on extreme ultraviolet spectra from double optical gating - Gilbertson, Steve; Mashiko, Hiroki; Li, Chengquan; Moon, Eric; Chang, Zenghu (My University, 2008)
Previously a two-color field was combined with a polarization gating to allow for the generation of single isolated attosecond pulses from multicycle lasers. Here, the scaling of energy for the extreme ultraviolet pulses corresponding to single attosecond pulses as a function of input laser pulse duration was investigated for argon, neon, and helium gas. Laser pulses as long as 12 fs were able to generate extreme ultraviolet supercontinua with high photon flux. The spectra profile depended strongly on the carrier envelope phase of the pump laser.